2019
DOI: 10.1017/s0007123418000534
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Positive and Negative: New Perspectives on Feedback Effects in Public Opinion on the Welfare State

Abstract: The study of policy feedback on public attitudes and policy preferences has become a growing area of research in recent years. Scholars in the tradition of Pierson usually argue that positive, self-reinforcing feedback effects dominate (that is, attitudes are commensurate with existing institutions), whereas the public thermostat model developed by Wlezien and Soroka expects negative, self-undermining feedback. Moving beyond the blunt distinction between positive and negative feedback, this article develops an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 70 publications
(128 reference statements)
1
79
0
1
Order By: Relevance
“…A final remark is that this study has demonstrated the existence of shortterm feedback effects. The question remains if this process will also give rise to feedback effects that reinforce a long-term development path (Busemeyer et al 2019). In the case of Swedish welfare policy, such development could imply a turn of the "policy mood" in direction of a more restrictive privatization policy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A final remark is that this study has demonstrated the existence of shortterm feedback effects. The question remains if this process will also give rise to feedback effects that reinforce a long-term development path (Busemeyer et al 2019). In the case of Swedish welfare policy, such development could imply a turn of the "policy mood" in direction of a more restrictive privatization policy.…”
Section: Discussionmentioning
confidence: 99%
“…Wlezien 1995, see further below) where individuals are found to adapt their opinions in relation to policy change, there is according to research overviews on policy feedback by Campbell (2012) as well as Larsen (2018) inconclusive evidence that changes in policies result in changes in opinion. Busemeyer et al (2019) suggest that some of the disagreements and contradictions of previous research is due to conceptual ambiguity, where research, for example, focus on different time perspectives.…”
Section: Public Responsivenessmentioning
confidence: 99%
“…Voters should only react to different fiscal policies if they also care about them. Third, it enables us to study elite responsiveness to public opinion more carefully (e.g., Busemeyer et al, 2020;Hager and Hilbig, 2020). Governments may be equally responsive to all citizens' policy positions, but they can still give more weight to the priorities of high-than low-income people (Bartels, 2018).…”
Section: Fiscal Consolidation and Public Opinion: Do Citizens Have Inmentioning
confidence: 99%
“…Thus, generous childcare policies appear to generate selfreinforcing feedback effects which increase overall support and acceptance of these policies (cf. Busemeyer et al, 2019;Neimanns, 2020).…”
Section: Determinants Of Attitudes and Preferences Towards Childcarmentioning
confidence: 99%
“…2 We take into account all types of public and private forms of formal early childhood education and care for the whole age range from age zero up to the beginning of compulsory schooling. 3 Inspired by the extensive literature on policy feedback (Busemeyer, Abrassart, & Nezi, 2019), we expect that attitudes and preferences are strongly shaped by institutional contexts, that is, the availability and affordability of childcare. The analysis in this article makes use of the INVEDUC ('Investing in Education in Europe') survey (Busemeyer, Garritzmann, Neimanns, & Nezi, 2018), which is a representative survey of public opinion in Western European countries (United Kingdom, Ireland, Sweden, Denmark, Italy, Spain, Germany and France) conducted in 2014.…”
Section: Introductionmentioning
confidence: 99%